KNOWLEDGE TRANSMISSION OF PALEMBANG ISLAMIC ULAMA DURING PALEMBANG SOULTANATE TO COLONIAL ERA - Herlina Herlina (Journal of Malay Islamic Studies, 2019)
This historiography reveals the transmission of Islamic knowledge historically carried out by Palembang intellectuals, who lived during the Palembang sultanate and still prevailed until the Colonial era, after the Palembang sultanate had fallen and changed to the Palembang residency. This recording history uses historical methods, e.i. heuristics, source criticism, auffassung, and derstallung, while in data analysis it was used social hermeneutics and philological research stages. The results of historical sources, both texts and references which related to the problem of knowledge transmission of Palembang Islamic cleric, identified some Palembang Ulama in this period in transmitting knowledge. They were Shaykh Syihabuddin al-Jawi al-Palembani, Kemas Fakhruddin, Shaykh Sharia Abdus-Samad al-Palimbani, Shaykh Azhary Abdullah, Shaykh Kemas Azhary, and Azhary Imam. Knowledge Transmission of Palembang Ulama consists of two ways; Da'wah Bi Lisan and Da'wah Bi Qalam with scientific fields that include Fikih Akhlak, Tasawuf and Falak, Qur’an and Hadith, Islamic social and culture, Islamic history and Islamic biographies, prayer and remembrance, as well as jihad.